North Africa Arabic Women’s Attitudes Towards Openness to Change - Abulhul, Zeinab (Technium Social Sciences Journal, 2021)
This article aims to identify some social factors on North Africa Arabic women’s attitudes towards openness to change. This study used a quantitative research method using multiple linear regression to explore the relationship between education level, social status, age, and gender as independent variables, and openness to change as a dependent variable. The research used the following questions to examine attitudes of the Arabic women in North Africa toward openness to change; Are there differences between Arabic men and women in their openness to change scores? Is there a positive relationship between education and Arabic women’s openness to change? Does social class influence Arabic women’s attitudes toward openness to change? Is there a relationship between Arabic women’s age and openness to change? The results showed differences between Arabic women’s and Arabic men’s attitudes toward openness to change. Also, the author found that Arabic older women attitudes who were aged from 46 to 67 years old were more open to change than Libyan younger women attitudes who were aged between 35 to 45 years old to openness to change.